2018
DOI: 10.1097/igc.0000000000001221
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Extended Bevacizumab Therapy in Elderly (≥70 Years) Versus Younger Patients Treated for Newly Diagnosed Ovarian Cancer in the International ROSiA Study

Abstract: Bevacizumab-treated patients aged 70 years or older had higher incidences of anemia, low-grade diarrhea, and asthenia, and grade ≥3 hypertension and thromboembolic events than those younger than 70 years, but no other relevant increase in toxicity. Median PFS of approximately 2 years is similar to that in younger patients despite the worse prognosis. Older age should not preclude bevacizumab therapy for ovarian cancer in carefully selected patients aged 70 years or older. Given the higher background hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
4
22
1
1
Order By: Relevance
“…This finding is consistent with published safety results from the GEICO 1205 and ANTHALYA randomized phase II trials evaluating neoadjuvant bevacizumab; neither identified any particular safety concerns with neoadjuvant administration of bevacizumab 10 11. Hypertension and thromboembolic events were slightly more common in older than younger patients; this finding is consistent with the known increased risk of these events in older patients and those with pre-existing hypertension, irrespective of treatment, and is also consistent with findings from the ROSiA study 12…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with published safety results from the GEICO 1205 and ANTHALYA randomized phase II trials evaluating neoadjuvant bevacizumab; neither identified any particular safety concerns with neoadjuvant administration of bevacizumab 10 11. Hypertension and thromboembolic events were slightly more common in older than younger patients; this finding is consistent with the known increased risk of these events in older patients and those with pre-existing hypertension, irrespective of treatment, and is also consistent with findings from the ROSiA study 12…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the two age groups did not significantly differ in PFS or OS. Several previous reports have suggested that the efficacy of bevacizumab-containing therapy is similar in older and younger patients with ovarian cancer (15)(16)(17). Although these reports investigated treatment with bevacizumab in combination with other cytotoxic agents, the results are consistent with our study, which evaluated bevacizumab monotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…To date, the tolerability of bevacizumab therapy in older ovarian cancer patients has only been investigated in a limited number of studies. Selle et al have evaluated bevacizumab-containing therapy tolerability when used as a first-line treatment in older patients with ovarian cancer (17). The findings of their study indicated that there were higher incidences of all grade anemia, diarrhea, and grade ≥3 hypertension, and thromboembolic events in ovarian cancer patients aged ≥70 years as compared to those <70 years.…”
Section: Discussionmentioning
confidence: 99%
“…Median PFS was similar (23.7 versus 25.6 months) to that in younger patients despite the worse prognosis. Older age should not preclude bevacizumab therapy for ovarian cancer, but elderly patients should be monitored more closely while receiving bevacizumab (26). There are many others ongoing clinical trials that investigate the role of bevacizumab in combination with other targeted drugs in first line therapy setting.…”
Section: Discussionmentioning
confidence: 99%